A study of strategy, organization structure and performance of insurance firm: A case study of Takaful Malaysia - Wong, Patrick Chang Yang (2014)
Syarikat Takaful Malaysia Berhad (STMB) has been in the insurance industry for more than 28 years but the company's performance has not been encouraging. However, since 2009 there has been a major transformation initiative taken by the company. The transformation looks at the following perspectives; "People and Leadership", "Process and Best Practices" and "Technology and Systems", and how they supported the company's strategy. This research is to investigate on how to transform Takaful Malaysia from being reactive to the market, and realign itself to be business focused by looking at the people, leadership, process, best practices, systems and technologies. It will also explore all the initiatives that had taken place from 2009 to 2012, by looking at the said three components described earlier. Some of the theories used include Change Management theories, Leadership theories and the Porter 5-forces theories, which include Force Field Analysis Approach, Rational Approach to Change, Emotional Approach, Porter's Value Chain Model and military strategy theories such as Sun Tzu, Genghis Khan and US Marines. We had conducted a survey with the Management team, and 12 had responded out of 13. The other person was out of country and hence, we will exclude the response from the 13th candidate. The breakdown of the analysis from the responses are as follows:- ■ 3 respondents are from sales division, which are also the initiatives driver of the company and income generating divisions. ■ 1 respondent is from investment unit, which is also income generating division. Do note that these 4 divisions mentioned above are the one generating actual income and sales for the company. They are the key business units that require the most support in order to achieve the top line. As for the rest of the divisions:- • 2 respondents are from insurance operations • And the rest of the 6 respondents are from supporting divisions